PENANAMAN NILAI–NILAI PANCASILA UNTUK MENCEGAH TINDAKAN KORUPSI BAGI MAHASISWA DI MASA DEPAN - Khoirunnisak, Anis; Shaghifa, Baiat Anninur; Meta, Asalia Claudio (Journal of Democratia, 2024)
The aim of this research is to explain the implementation of instilling Pancasila values ?? in the context of preventing acts of corruption for students in the future. This research uses a qualitative, descriptive research approach. Data sources were obtained from student informants, places, events and documents. Data collection techniques using interviews, observation and document analysis. Based on the research results, it can be concluded that 1). The application of Pancasila values ?? to prevent acts of corruption for Ivet University students is: a) The first principle which says "God is Almighty" if we commit acts of corruption it means we have lied or lied to God. b) The second principle which reads "Just and Civilized Humanity" by committing corruption means that you have committed an act that makes your position a place to get what you want for your own happiness and also harms other people because of it. c) The third principle which states "Indonesian Unity" is that corruption is an act that can destroy public trust, resulting in the public feeling intimidated and not caring about the actions taken by the government. d) The fourth principle which states "The People Are Guided by Wisdom in Deliberation and Representation" with corruption is the same as taking action based on one's own decisions and that is not good because determining and doing everything must be based on mutual agreement. e) The fifth principle which states "Social Justice for All Indonesian People" is to be fair to others and respect every right that the Indonesian people have. Corruption shows injustice between the government and society